Survival Implications Associated with Variation in Mastectomy Rates for Early-Staged Breast Cancer. (8th August 2012) - Brooks, John M.; Chrischilles, Elizabeth A.; Landrum, Mary Beth; Wright, Kara B.; Fang, Gang; Winer, Eric P.; Keating, Nancy L.
Abstract : Despite a 20-year-old guideline from the National Institutes of Health (NIH) Consensus Development Conference recommending breast conserving surgery with radiation (BCSR) over mastectomy for woman with early-stage breast cancer (ESBC) because it preserves the breast, recent evidence shows mastectomy rates increasing and higher-staged ESBC patients are more likely to receive mastectomy. These observations suggest that some patients and their providers believe that mastectomy has advantages over BCSR and these advantages increase with stage. These beliefs may persist because the randomized controlled trials (RCTs) that served as the basis for the NIH guideline were populated mainly with lower-staged patients. Our objective is to assess the survival implications associated with mastectomy choice by patient alignment with the RCT populations. We used instrumental variable methods to estimate the relationship between surgery choice and survival for ESBC patients based on variation in local area surgery styles. We find results consistent with the RCTs for patients closely aligned to the RCT populations. However, for patients unlike those in the RCTs, our results suggest that higher mastectomy rates are associated with reduced survival. We are careful to interpret our estimates in terms of limitations of our estimation approach.